Synthesis, Characterization, Theoretical and Experimental Anticancer Evaluation of Novel Cocrystals of 5-Fluorouracil and Schiff Bases against SW480 Colorectal Carcinoma - Farhat Jubeen; Ishrat Jabeen; Usman Aftab; Sadia Noor; Mah e Hareem; Misbah Sultan; Mohsin Kazi (MDPI AG, 2023)
The chemotherapeutic agent known as 5-fluorouracil (5-FU) is an artificial fluoropyrimidine antimetabolite that has been widely used for its antineoplastic properties. Cocrystals of 5-fluorouracil (5-FU) with five different Schiff bases (benzylidene-urea (BU), benzylidene-aniline (BA), salicylidene-aniline (SA), salicylidene-phenylhydrazine (SPH), and para-hydroxy benzylideneaniline (HBA)) are reported in this study. The newly synthesized cocrystals were analyzed by FTIR and PXRD. In this study, we investigated the antitumor efficacy of 5-FU derivatives in SW480 colon cancer cells via MTT assay at varying dose concentrations. Molecular docking was performed to predict the binding mechanism of TS with various 5-FU complexes. FTIR revealed the presence of respective functional groups in the prepared cocrystals. The frequencies (v) of N-H (3220.24 cm−1) and carbonyl groups (1662.38 cm−1) in the spectrum of 5-FU shifted considerably in all derivative cocrystal new interactions. There was a noticeable transformation in the PXRD peak of 5-FU at 2θ = 28.37° in all derivatives. The novelty of the present study lies in the fact that 5-FU-BA showed an anticancer potential IC50 (6.4731) far higher than that of 5-FU (12.116), almost comparable to that of the reference drug doxorubicin (3.3159), against SW480 cancel cell lines, followed by 5-Fu-HBA (10.2174). The inhibition rates of 5-FU-BA and 5-FU-HBA were highest among the derivatives (99.85% and 99.37%, respectively) in comparison with doxorubicin (97.103%). The results revealed that the synthesized 5-FU cocrystals have promising antitumor efficacy compared with previously reported 5-FU and 5-FU. The activities of the cocrystals were rationalized by a molecular modeling approach to envisage binding modes with the target cancer protein.